Calibration of a collinear backscattering Mueller matrix imaging system - Zhou, Xinrong; Fu, Yao; Liao, Helin; Chen, Zhenhua; Ji, Yanhong; Tang, Zhilie (Frontiers in Physics, 2023)
A collinear backscattering Mueller matrix (CBMM) imaging system has clear advantages in the detection of bulk biological tissues, which are highly scattering and depolarizing. Due to the double-pass configuration and noise in the system, the calibration of a collinear backscattering Mueller matrix imaging system is usually complex and of poor accuracy. In this work, we propose an alternative modified eigenvalue calibration method (ECM) based on the equivalent standard sample. For better noise suppression and higher calibration accuracy, we design the distribution of polarization states over the Poincaré sphere and solve for the parameters of equivalent standard samples by means of an optimization. Compared to other variants of the ECM used in the double-pass system, the accuracy of the proposed method is improved by more than 40 times. The comparison results with the error model-based calibration methods indicate that the modified ECM generally gives the best accuracy and precision, as well as the best reliability.